The evaluation and comparison on different types of resident doctors in training through DxR Clinician system. (June 2020) - Dong, Leilei; Li, Wei; Ma, Dedong; Lv, Chenguang; Chen, Cai
Abstract: Compared with the traditional problem-based learning (PBL) mode, computer-based case simulations (CCS) are more advanced in aspects of clinical reasoning, critical thinking and clinical thinking. CCS program, Diagnosis & Reasoning (DxR) Clinician, has been used for assessment of clinical diagnosis and treatment skills in more than 300 medical colleges and universities around the world. However, the evaluating effectiveness and practicability of this software continue to be uncertain and ambiguity in China. Moreover, the influence factors of the DxR evaluation score are still remain indefinite. The purpose of this study was to investigate the impact of training years, professional background and educational background on DxR scores in order to better improve the clinical skills of residents. Eighty one resident doctors were selected as the experimental subjects to conduct the clinical skills assessment with DxR Clinician. The relationships between residents' scores in DxR Clinician components (overall score, diagnostic score, and management score) and their training years, professional background and educational background were analysed using simultaneous regression. The results showed that years of training, professional background and educational background are potential influence factors of DxR evaluation score. The average DxR Clinician scores in this study are generally lower than foreign research, so we should strengthen resident standardized training to improve our clinical skills.